Psychological Impact and Coping Strategies of Dating Violence Among Late Adolescent Females in Surabaya: A Qualitative Study in an Urban Context - Ivanna Elizabeth Tania; Steven Killing; Juan Willfred Damuyilu Moekoe; Jefri Setyawan (Utan Kayu Publishing, 2026)
Dating violence among late adolescents has severe psychological consequences, yet research focusing on urban Indonesian contexts remains limited. This qualitative study explores the psychological impacts of dating violence and the coping strategies utilized by late adolescent females in Surabaya. Using a qualitative descriptive design within an interpretive paradigm, semi-structured interviews were conducted with three participants aged 19–20 years. Data were analyzed using Braun and Clarke’s thematic analysis. The findings reveal that early romantic expectations often mask the recognition of controlling behaviors, leading to normalization and escalation of violence. Participants reported profound psychological impacts, including anxiety, diminished self-esteem, and distrust. In navigating these impacts, coping strategies were heavily shaped by the urban social ecology of Surabaya; participants relied primarily on informal peer support and emotion-focused coping, while formal help-seeking and family disclosure were largely avoided due to fear of stigma and judgment. This study highlights the need for targeted, peer-led support programs, relationship education, and accessible, youth-friendly counseling services tailored to the urban adolescent context. Abstrak: Kekerasan dalam pacaran pada masa remaja akhir memiliki konsekuensi psikologis yang parah, namun penelitian yang berfokus pada konteks perkotaan di Indonesia masih terbatas. Penelitian kualitatif ini mengeksplorasi dampak psikologis kekerasan dalam pacaran dan strategi koping yang digunakan oleh remaja perempuan tahap akhir di Surabaya. Menggunakan desain deskriptif kualitatif dalam paradigma interpretif, wawancara semi-terstruktur dilakukan terhadap tiga partisipan berusia 19–20 tahun. Data dianalisis menggunakan analisis tematik Braun dan Clarke. Temuan menunjukkan bahwa ekspektasi romantis awal sering kali mengaburkan pengenalan terhadap perilaku mengontrol, yang berujung pada normalisasi dan eskalasi kekerasan. Partisipan melaporkan dampak psikologis yang mendalam, termasuk kecemasan, penurunan harga diri, dan krisis kepercayaan. Dalam mengatasi dampak tersebut, strategi koping sangat dibentuk oleh ekologi sosial perkotaan Surabaya; partisipan sangat bergantung pada dukungan teman sebaya (peer support) dan koping yang berfokus pada emosi, sementara pencarian bantuan formal dan keterbukaan pada keluarga dihindari karena takut akan stigma dan penghakiman. Penelitian ini menyoroti perlunya program dukungan berbasis teman sebaya, edukasi hubungan yang sehat, serta layanan konseling ramah remaja yang disesuaikan dengan konteks remaja perkotaan